Associations Between New Mothers' Demographics and Knowledge of FDA's Role in Supplement Regulation [7A]. (May 2016) - Baker, David A.; Crnosija, Natalie
Abstract : INTRODUCTION: Often recommended to improve maternal and fetal health, supplements do not require FDA approval to be sold or marketed. Demographic characteristics (i.e., education, income) are associated with supplement consumption; we investigated whether pregnant/recently pregnant women's demographics associate with knowledge of the FDA's role in supplement regulation. METHODS: The Stony Brook University Center for Survey Research distributed an online survey addressing supplements consumed, safety and regulation perceptions, and demographics, to pregnant/recently pregnant women (delivered within past 6 months) in the contiguous United States. We performed bivariate analysis to assess correlation between demographics and women's response to the question: "To the best of your knowledge does the Federal Food and Drug Administration (FDA) currently regulate dietary supplements?" Using multivariate logistic regression, we investigated associations between demographic variables and whether mothers responded "No" to the aforementioned question. RESULTS: With an analytic sample of 394, we found that women who selected friends, family, or co-workers as the most important supplement information source had a reduced odds of responding that the FDA does not regulate supplements, relative to those choosing healthcare providers as their most important information source (OR.37, CI=.16, .82). Women with an annual household income of less than $35, 000, relative to those with an annual $35, 000–$75, 000 income, had a reduced odds of reporting that the FDA does not regulate supplements (OR.45, CI=.21, .99). CONCLUSION: Our findings from this novel dataset demonstrate the need for healthcare providers to educate patients about supplement use during pregnancy to insure the proper nutrition and safety of mothers and their babies.